Search for CP violation in B+/- --> J/psiK+/- and B+/- --> psi(2S)K+/- decays. - Bonvicini, G; Cinabro, D; McGee, S; Perera, L; Zhou, G; Lipeles, E; Pappas, S; Schmidtler, M; Shapiro, A; Sun, WM; Weinstein, A; Jaffe, D; et al. (2000)
We present a search for direct CP violation in B+/--->J/psiK+/- and B+/--->psi(2S)K+/- decays. In a sample of 9.7x10(6) BandBmacr; meson pairs collected with the CLEO detector, we have fully reconstructed 534 B+/--->J/psiK+/- and 120 B+/--->psi(2S)K+/- decays with very low background. We have measured the CP-violating charge asymmetry to be [+1.8+/-4.3(stat)+/-0.4(syst)]% for B+/--->J/psiK+/- and [+2.0+/-9. 1(stat)+/-1.0(syst)]% for B+/--->psi(2S)K+/-.